Análise da legislação para cisternas pluviais no município de Concórdia - Vaz, Sandra Miwa Wronka (2015)
This study aims to evaluate the municipal law that defines the mandatory installation of rainwater tanks, taking steps that lead to sustainability, rational use, decrease in quantity of waste water and mitigation of runoff from heavy rains. Urban drainage, one of sanitation elements, only receives attention in the event of flooding and consequently damage to property. It is necessary for urban managers to have an integrated vision, aligning the structural works and preventive measures, seeking the control and management of rainwater. The study analysed rules used in several cities, and the parameters adopted. The volumes defined by the law were compared with the volumes calculated by the rule methods and the rational method, and results were assessed. The importance of correct dimensioning of these batch levels in reservoirs is part of non-structural actions, which act as a preventive measure in order to minimize the negative impacts of soil sealing associated with the increasing urban population. The municipal legislation should be technically supported, and must define solutions that are compatible with local characteristics and the characteristics of the hydrographic basin in which the city is located, promoting discussion of solutions and contributing to the implementation of efficient and sustainable projects.